On the Adomian Decomposition Method and its Applications to Mechanics - Nedjem Eddine Benchouia; Belgacem MADI; Mohamed Rafik SARI; Azzedine BOUZAOUIT (5ème Conférence Internationale sur la maintenance et la sécurité Industrielle (CIMISI’2019), 2019)
In this paper, we review the Adomian decomposition method (ADM). We give a general description of this method and we present some modifications for the standard Adomian decomposition method. Application is made to Blasius problem, a dissipative wave equation, and free vibration of Euler-Bernoulli beam. The results obtained have been discussed and shows the effectiveness of the method.
Sur la méthode de décomposition d’Adomian et ses applications en mécanique